2017
DOI: 10.1016/j.pharmthera.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase as a therapeutic target for pain, inflammatory and neurodegenerative diseases

Abstract: Eicosanoids are biologically active lipid signaling molecules derived from polyunsaturated fatty acids. Many of the actions of eicosanoid metabolites formed by cyclooxygenase and lipoxygenase enzymes have been characterized, however, the epoxy-fatty acids (EpFAs) formed by cytochrome P450 enzymes are newly described by comparison. The EpFA metabolites modulate a diverse set of physiologic functions that include inflammation and nociception among others. Regulation of EpFAs occurs primarily via release, biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
204
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 225 publications
(231 citation statements)
references
References 192 publications
(205 reference statements)
6
204
0
2
Order By: Relevance
“…Podocyte‐specific sEH deficiency reduces ER stress and renal fibrosis under hyperglycaemia (Bettaieb et al, ). Inhibition of sEH stabilizes epoxy fatty acids to reverse ER stress (Wagner et al, ). Similar to these findings, we confirm that sEH can positively regulate ER stress in the renal cortex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Podocyte‐specific sEH deficiency reduces ER stress and renal fibrosis under hyperglycaemia (Bettaieb et al, ). Inhibition of sEH stabilizes epoxy fatty acids to reverse ER stress (Wagner et al, ). Similar to these findings, we confirm that sEH can positively regulate ER stress in the renal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Podocyte-specific sEH deficiency reduces ER stress and renal fibrosis under hyperglycaemia (Bettaieb et al, 2017). Inhibition of sEH stabilizes epoxy fatty acids to reverse ER stress (Wagner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we observed that the fold-change was much more pronounced with the enantiomers than with the total levels of the corresponding regioisomers. This shift in enantiomeric composition has not been analyzed before, but might have significantly contributed to the beneficial effects of genetic or pharmacological sEH inhibition as observed in various animal models of cardiovascular and inflammatory diseases (24,25,39,40). Also, the enantioselectivity of mEH may provide a novel clue for understanding the role of this enzyme in human diseases (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that increased expression of antioxidant enzymes and reduction in ROS production mediated by EETs [137, 140] may lead to decreased ER stress. Thus, additional studies are needed to decipher the precise molecular mechanisms underlying regulation of ER stress by sEH and the contribution of ER stress to the beneficial effects of sEH deficiency and inhibition [141]. …”
Section: Modulation Of Er Stress By Soluble Epoxide Hydrolasementioning
confidence: 99%